2008
DOI: 10.1037/a0012821
|View full text |Cite
|
Sign up to set email alerts
|

Retaliation as a response to procedural unfairness: A self-regulatory approach.

Abstract: When does procedural unfairness result in retaliation, and why do unfair-treatment recipients sometimes pursue and other times inhibit retaliation? Five studies addressed these questions. We proposed and found that regulatory focus moderates retaliation against an unfairness-enacting authority: Promotion-focus participants were more likely to retaliate than prevention-focus participants. Promotion focus was associated with, and also heightened the accessibility of, the individual self. In turn, individual-self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
55
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 104 publications
(199 reference statements)
7
55
0
1
Order By: Relevance
“…THE JOURNAL OF SOCIAL PSYCHOLOGY Our findings are entirely consistent with other research on reactions to unfairness, selfishness, and disrespect (e.g., Allen & Leary, 2010;Bembenek et al, 2007;Brebels et al, 2008;Cohen et al, 1996;Colquitt, Conlon, Wesson, Porter, & Ng, 2001;Miller, 2001;Stephenson et al, 2011) but extend previous thinking. From our perspective, perceived unfairness and disrespect evoke strong reactions to otherwise trivial events because they are among the most common-and perhaps the most potentially harmful-violations of social exchange rules.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…THE JOURNAL OF SOCIAL PSYCHOLOGY Our findings are entirely consistent with other research on reactions to unfairness, selfishness, and disrespect (e.g., Allen & Leary, 2010;Bembenek et al, 2007;Brebels et al, 2008;Cohen et al, 1996;Colquitt, Conlon, Wesson, Porter, & Ng, 2001;Miller, 2001;Stephenson et al, 2011) but extend previous thinking. From our perspective, perceived unfairness and disrespect evoke strong reactions to otherwise trivial events because they are among the most common-and perhaps the most potentially harmful-violations of social exchange rules.…”
supporting
confidence: 82%
“…First, people become angry when they perceive that others have treated them unfairly (Bembenek, Beike, & Schroeder, 2007;Brebels, De Cremer, & Sedikides, 2008). People sometimes react to unfairness even when it does not matter (Allen & Leary, 2010), and perceptions of procedural justice and fairness are enhanced when people have an opportunity to voice their views even when their input cannot affect the outcome (Lind, Kanfer, & Earley, 1990;Tyler, 1987;Tyler, Rasinski, & Spodick, 1985).…”
mentioning
confidence: 99%
“…2 The use of difference scores is a common approach for the data analyses of regulatory orientation questionnaires (e.g., Brebels & De Cremer, 2008;Cesario, Grant, & Higgins, 2004;Fransen, Fennis, Pruyn, & Vohs, 2011;Higgins et al, 2001;Keller, & Bless, 2006;Lockwood et al, 2002;Santelli et al, 2009). In our experiments, we decided to use the difference scores approach because, from a theoretical point of view, regardless of the strength of each orientation, it is the relative strength that determines, across situations, the sensitivity to promotion or prevention suggestions.…”
Section: Methodsmentioning
confidence: 99%
“…Urging caution in the interpretation of findings for the Lockwood et al (2002) instrument, Summerville and Roese (2008) suggested that this instrument "functions like a measure of approach and avoidance (the BIS/BAS [Behavioral Inhibition Scale/Behavioral Activation Scale])" (Carver & White, 1994). We nevertheless employed the Lockwood et al instrument because (a) it has good face validity, with items that are clearly linked to the theoretical definitions of promotion and prevention orientation; (b) it has good psychometric properties, with demonstrated reliability and validity; and (c) it is one of the most frequently employed means of assessing dispositional regulatory orientation (e.g., Brebels & De Cremer, 2008;Keller & Bless, 2006;Lockwood, Marshall, & Sadler, 2005;McGregor, Gailliot, Vasquez, & Nash, 2007;Murray, Derrick, Leder, & Holmes, 2008;Oyserman, Uskul, Yoder, Nesse, & Williams, 2007). Two additional points are relevant to the Summerville and Roese cautionary note: (d) In prior work we have found that associations with promotion and prevention as assessed using the Lockwood et al instrument are not attributable to approach or avoidance tendencies (BIS/BAS scores; Righetti et al, 2010); and importantly, (e) the existence of moderate associations of promotion and prevention with approach or avoidance and/or positive versus negative affect should not be regarded as problematic, but rather as inherent properties of these constructs.…”
Section: Methodsmentioning
confidence: 99%
“…Recently it has been argued that these and other findings suggest that affective reactions to fair and unfair events probably have something to do with processes of self-regulation (e.g., Brebels, De Cremer, & Sedikides, 2008;Miedema, Van den Bos, & Vermunt, 2006;Van den Bos, Ham, Lind, Simonis, Van Essen, & Rijpkema, 2008;Van den Bos & Lind, 2002Van Prooijen & Zwenk, 2009). For example, Miedema et al (2006) proposed that fairness can be a means of selfdefense and that situations that are threatening to the self therefore should lead people to react in stronger affective terms to fair and unfair events.…”
mentioning
confidence: 99%